(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This study underscores the importance of cognitive linguistics in analyzing proverbs as windows into cultural cognition. By comparing English and Uzbek proverbs through this lens, we enrich our understanding of how language shapes thought while fostering greater appreciation for cultural diversity.